CURRENT SITUATION AND SOME FACTORS RELATED TO SIGNS OF ANXIETY IN HIGH SCHOOL FINALISTS IN HANOI CITY (Vietnam Journal of Community Medicine, 2026)
A cross-sectional study on 986 grade 12 students, high school level in Hanoi city from March 1, 2024 to May 30, 2024. The research objective is to determine the rate and some factors related to signs of anxiety in high school seniors in Hanoi city. Results: the level of mild anxiety signs is 27.28%, moderate anxiety signs are 10.95%, severe anxiety signs are 6.69%. Factors that are statistically significant with the rate of students showing signs of anxiety are: Gender, academic pressure, mental bullying, phone addiction (p
Keywords: Anxiety; smartphone addiction; bullying; academic pressure; final-year high school students; 12th-grade students